2011
DOI: 10.1038/nn.2887
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating monocytes trigger EAE progression, but do not contribute to the resident microglia pool

Abstract: In multiple sclerosis and the experimental autoimmune encephalitis (EAE) mouse model, two pools of morphologically indistinguishable phagocytic cells, microglia and inflammatory macrophages, accrue from proliferating resident precursors and recruitment of blood-borne progenitors, respectively. Whether these cell types are functionally equivalent is hotly debated, but is challenging to address experimentally. Using a combination of parabiosis and myeloablation to replace circulating progenitors without affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
842
5
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 938 publications
(910 citation statements)
references
References 49 publications
61
842
5
2
Order By: Relevance
“…3D), supporting the idea that CCR2 mediates an important role in monocyte infiltration into the brain. Iba1 is expressed by brain-invading monocytes, but only after the monocytes have entered the brain and undergone maturation (35), so the reduced number of Iba1 + myeloid cells in the CCR2-deficient mice (Fig. 3C) can be quantitatively accounted for by the loss of invading monocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D), supporting the idea that CCR2 mediates an important role in monocyte infiltration into the brain. Iba1 is expressed by brain-invading monocytes, but only after the monocytes have entered the brain and undergone maturation (35), so the reduced number of Iba1 + myeloid cells in the CCR2-deficient mice (Fig. 3C) can be quantitatively accounted for by the loss of invading monocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is conceivable that the invading monocytes are still present in the brain, but are not detectable by using CCR2-RFP as a marker because of down-regulation. Another possibility is that the monocytes have died, as blood-borne myeloid cells do not engraft the brain on a long-term basis in EAE models (35). Nevertheless, the absence of CCR2-RFP + monocytes at the 14-d time point indicates that brain recruitment of blood-borne monocytes is transient, limited to the first few days after SE, and has ceased 2 wk after SE, suggesting the inflammatory processes responsible for and involving monocyte recruitment have resolved by the 2-wk time point.…”
Section: Discussionmentioning
confidence: 99%
“…The latter groups of cells appear crucial in determining the severity of the acute inflammatory phase of the disease. Contribution of monocytes to the acute inflammatory phase and progression of disease has recently been strengthened by a group using parabiotic animals to show that compromise of the blood-brain barrier and subsequent invasion of the CNS by inflammatory monocytes are the key events in promoting disease progression in EAE (7). The EAE model is not an exact model of the human disease, particularly in terms of the natural clinical progression.…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of this infiltration could be deleterious, for example, in the release of NO and TNF-a from TipDCs in severe influenza viral infection (5), or beneficial, as in a model of spinal cord injury where the recruitment of Ly6C + monocytes aided tissue repair (6). A recent study has shown that infiltrating Ly6C + monocytes have fundamentally different role from microglia (7). Although microgliosis could be an initial step in pathogenesis of experimental autoimmune encephalomyelitis (EAE), infiltrating monocytes appear more involved in the acute phase of EAE, which occurs as relapses in the relapsing-remitting form of the human disease (MS).…”
mentioning
confidence: 99%
“…Regardless, it is clear that BMderived monocyte invade the damaged CNS and retina; what is unclear is whether they linger or differentiate into microglia, which occurs during development. A recent study suggested that BM-derived monocytes recruited to the CNS during experimental autoimmune encephalitis do not eventually contribute to the pool of resident microglia unless they were transplanted, and that this is due to the lineage uncommitted nature of the injected BM cells [20].…”
Section: Introductionmentioning
confidence: 99%